2016
DOI: 10.1039/c5ra25232f
|View full text |Cite
|
Sign up to set email alerts
|

In vitro human gastro-intestinal enzyme digestibility of globulin isolate from oil palm (Elaeis guineensis var. tenera) kernel meal and the bioactivity of the digest

Abstract: Theex vivohydrolysate of oil palm kernel globulin isolate exhibit bioactivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 38 publications
2
11
0
1
Order By: Relevance
“…These results showed that PIs are not resistant to digestive proteases. Similar results were reported for other digests of plant proteins obtained from almond (Sze-Tao and Sathe, 2000) and oil palm kernel (Tapal et al, 2016)…”
Section: Digestibility Of Protein Isolatesupporting
confidence: 90%
“…These results showed that PIs are not resistant to digestive proteases. Similar results were reported for other digests of plant proteins obtained from almond (Sze-Tao and Sathe, 2000) and oil palm kernel (Tapal et al, 2016)…”
Section: Digestibility Of Protein Isolatesupporting
confidence: 90%
“…The study by Tapal et al . () describes the ex vivo digestibility of globulin isolate prepared from oil palm kernel. The hydrolysate, obtained by in vitro human gastrointestinal enzyme digestibility of the globulin isolate, exhibited potent ACE inhibitory activity (IC 50 = 50 μg mL −1 ) and anticancer activity against human colon epithelial cancer HT‐29 cells and hepatocarcinoma HepG2 cells (Tapal et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…() describes the ex vivo digestibility of globulin isolate prepared from oil palm kernel. The hydrolysate, obtained by in vitro human gastrointestinal enzyme digestibility of the globulin isolate, exhibited potent ACE inhibitory activity (IC 50 = 50 μg mL −1 ) and anticancer activity against human colon epithelial cancer HT‐29 cells and hepatocarcinoma HepG2 cells (Tapal et al ., ). Another important group of peptides are anti‐inflammatory peptides, as the inflammatory process is fundamental to a number of diseases, for example cancers or cardiovascular disease (Chakrabarti et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…19 However, both ADVFNPR and LVYIIQGR exhibited higher antioxidant activity than the smaller peptides from rice residue (464.2 Da, IC 50 : 43.55 mg mL À1 ), 22 tilapia protein (317.3 Da, IC 50 : 26.4 mg mL À1 ) 6 and walnut protein (423.23 Da, IC 50 : 310.0 mg mL À1 ), 3 indicating that antioxidant activity of peptides was not dependent only on M w . Moreover, Tapal et al 12 also obtained the peptide ADVFNPR from palm kernel globulin and found that it had antihypertensive and anticancer activity. It was demonstrated that antioxidant activity of peptides is positively correlated with the hydrophobic property.…”
Section: Characterization Of Puried Peptidesmentioning
confidence: 99%
“…10 It was found that enzymatic hydrolysates of the globulin showed anticancer, antihypertensive and antibacterial activities; also several peptides obtained from the glutelin-2 could effectively lower the systolic blood pressure of spontaneously hypertensive rats. [11][12][13] Dilute acid-soluble seed storage proteins are commonly known as glutelin-1 proteins. 14 A previous study has demonstrated that palm kernel expeller glutelin-1 (PKEG-1) exhibited high scavenging activity of DPPH radical (77.69%), ABTS radical (64.19%), superoxide radical (49.54%) and hydroxyl radical (34.41%); also it exhibited high reducing power (0.211 AE 0.009), 10 indicating that antioxidant peptides could be isolated from it.…”
Section: Introductionmentioning
confidence: 99%